Manajemen Pengelolaan Desa Wisata Kelor Slamen Yogyakarta: Desa Wisata - Rahmawati; Matius Tinna Sarira; Faradila Anggun Surya Rini; Hastuti Nurhayati; Wawan Kurniawan (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Abstract. This study examines the development model for rural tourism destinations, focusing on Kelor Village in Sleman, Yogyakarta. As a rural tourism area, Kelor Village combines natural beauty with unique cultural elements, making it an attractive destination. This research aims to analyze the organizational structure of the village's tourism management, the collaboration between stakeholders in decision-making processes, and the policies implemented to enhance the effectiveness of stakeholder roles in sustainable tourism development. Using a qualitative descriptive approach, data was collected through in-depth interviews, observations, and document analysis. The study reveals that Kelor Village’s tourism management involves multiple stakeholders, including local residents, government bodies, and private sector actors. However, challenges such as limited resources and competition with neighboring villages affect the village's ability to provide consistent, high- quality services. The findings suggest that improving stakeholder collaboration, enhancing infrastructure, and offering regular training could strengthen Kelor Village’s position as a sustainable tourism destination. This research contributes to the literature on rural tourism management by highlighting the importance of community involvement and collaborative policy-making for long-term success. Keyword:Tourism Management, Stakeholder Collaboration, Kelor Tourism Village